Konteksasi Ushul Fiqh dalam Hukum Nasional Indonesia: Pelestarian Laut dan Pengembangan Industri Wisata Bahari - Fikri, Fikri (LPPM IAIN Parepare, 2022)
This study aims to explain the context of ushul fiqh in Indonesian national law for the development of the marine tourism industry. consists of two issues, namely enforcement of Indonesian national law in the development of the marine tourism industry, and harmonization between ushul fiqh and Indonesian national law in the development of the marine tourism industry. This study uses a qualitative descriptive approach and data analysis with law enforcement theory, positive law theory and the theory of “maqasid al-shariah” in Islamic law. This research was conducted at a water location in Bone Regency for six months. The results of this study indicate that enforcement of Indonesia's national law for the development of the marine tourism industry is an effective strategy from the government to maintain balance and security of marine ecosystems from degradation, the northwest conservation area becomes a marine tourism industry in order to be more innovative and productive in improving the economy of fishing communities, prevent damage to the sea area as an ecosystem. The harmonization of ushul fiqh in Indonesian national law is in harmony through the study of